STRUKTUR DIFERENSIAL KRUSKAL-SZEKERES SEBAGAI SEBUAH EKSOTIKA DI R4 DAN PERUMUSAN PERSAMAAN MAXWELL PADANYA - , MUQOYYANAH; , Dr. rer. nat. Muhammad Farchani Rosyid. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Exotica on four-dimensional topological space has been analyzed. Based on existing studies, there is no explicitly exoticaâs example has mentioned on R4 topological space. Based on calculations with end-sum Gompf technique, it has shown that Kruskal-Szekeres coordinate system represents a differential structure which is not diffeomorphic (equivalent) with a standard differential structure on R4. This result makes different formulation of physics laws as the consequence. One of an example is on electrodynamics formulation through Maxwell equations. Relativistic Maxwell equations are derived on this exotic manifold.